SOCIO-PSYCHOLOGICAL FACTORS OF ADAPTATION (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
The article discusses the psychological changes of adolescence, the problem of adaptation, adaptation, emotional experiences in them, learning, sensitivity, educational activities, the desire for activity and independence in adolescents, communication with peers.